Loratadine, an H1 Antihistamine, Inhibits Melanogenesis in Human Melanocytes. (17th March 2019) - Moon, Hye-Rim; Jo, Soo Youn; Kim, Hak Tae; Lee, Woo Jin; Won, Chong Hyun; Lee, Mi Woo; Choi, Jee Ho; Chang, Sung Eun
Abstract : It has long been believed that histamine is associated with cutaneous melanogenesis. Specifically, H2-receptor antagonists reportedly inhibit melanogenesis, but H1-receptor antagonists, which are some of the most commonly prescribed medicines in dermatology, have not been studied to determine whether and how they regulate melanogenesis. Therefore, we screened H1-receptor antagonists to determine whether they inhibit melanogenesis and found that loratadine was particularly effective, in this regard without compromising cellular viability. Loratadine downregulated microphthalmia-associated transcription factor (MITF) and tyrosinase in melanocytes. To determine the intracellular signaling pathways, Akt was consistently activated by loratadine. PI3K/Akt pathway inhibitor, LY294002, restored the reduced melanin content that was induced by loratadine. In addition, phospho-GSK-3 β also was found to be increased following loratadine treatment. Loratadine reduced the amount of PKC- β II in the membrane fraction, thereby decreasing its activity. Taken together, our data indicate that loratadine regulates melanogenesis via Akt/MITF and PKC- β II signaling, thereby leading to the inhibition of melanogenic proteins. The antimelanogenic effects of loratadine have potentially significant and useful roles in dermatologic practice, although further clinical studies will be required to test this.